Cell Proliferation Activity and Prognostic Index in Squamous Cell Lung Carcinoma - José Antonio Alvarez-Riesgo; Andrés Sampedro; Radhamés Hernández; María Victoria Folgueras; Ana Salas-Bustamante; Antonio Cueto (Analytical Cellular Pathology)
Flow Cytometry (FC) has been incorporated into cancer research in relation to its prognostic value together with histological parameters and TNM stages. We have studied by means of FC the cell cycle of 132 samples from male patients with Squamous Cell Lung Carcinoma (SQCLC). All of the patients received curative surgery and the clinical follow-up was 60 months. The clinical and cytometric parameters were evaluated in order to predict the patients’ outcome. The presence of tumoural recurrence and the tumoural stage showed statistical significance associated with survival. The multivariant analysis reveals radiotherapy (p = 0.004) as protective variable and the high S-phase fraction (SPF) (p = 0.001) and stage IIIA (p = 0.012) as risk factors. The SPF appears as an independent prognostic factor for overall survival time. We can build a prognostic index representative of different prognostic groups, which allows us to improve the individual monitoring of these patients.